2012
DOI: 10.1089/ars.2011.4327
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin and Glutaredoxin Systems in Plants: Molecular Mechanisms, Crosstalks, and Functional Significance

Abstract: Thioredoxins (Trx) and glutaredoxins (Grx) constitute families of thiol oxidoreductases. Our knowledge of Trx and Grx in plants has dramatically increased during the last decade. The release of the Arabidopsis genome sequence revealed an unexpectedly high number of Trx and Grx genes. The availability of several genomes of vascular and nonvascular plants allowed the establishment of a clear classification of the genes and the chronology of their appearance during plant evolution. Proteomic approaches have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
261
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(287 citation statements)
references
References 259 publications
3
261
0
6
Order By: Relevance
“…In fact, the cross-talk between the Trx and Grx systems with the catalytic disulfide of some plant Trxs reduced by the Grx systems has been reported previously, such as poplar Trx h4 (33,34), Arabidopsis thaliana Trx h9 (35), and grape Trx h (Vitis vinifera CxxS2) (36). According to the authors, the reduction of plant Trx by the Grx system is a deglutathionylation reaction (37), which is as same as the mechanism proposed in our study.…”
Section: Discussionsupporting
confidence: 87%
“…In fact, the cross-talk between the Trx and Grx systems with the catalytic disulfide of some plant Trxs reduced by the Grx systems has been reported previously, such as poplar Trx h4 (33,34), Arabidopsis thaliana Trx h9 (35), and grape Trx h (Vitis vinifera CxxS2) (36). According to the authors, the reduction of plant Trx by the Grx system is a deglutathionylation reaction (37), which is as same as the mechanism proposed in our study.…”
Section: Discussionsupporting
confidence: 87%
“…With the exception of SO 3 H, all the other oxidized forms of cysteine residues can be reversibly reduced by glutaredoxins (GRXs), thioredoxins (TRXs) or sulfiredoxins (SRXs). [113][114][115][116] A large body of evidence indicates that plant transcription factors involved in stress acclimation and development can operate as direct targets of these posttranslational modifications. 98,117,118 Several different mechanisms are employed by plants to achieve the redox control of transcription factor activities, which encompass redox-modulated subcellular compartmentation, redox-regulated conformational changes, redox-controlled assembly with coregulators, oxidative disassembly of metal-sulfur clusters, indirect redox effects on posttranslational modifications, redox-triggered proteolytic processing, and direct control of DNA binding.…”
Section: Redox Regulation Of Tcp Proteinsmentioning
confidence: 99%
“…In plants, cellular redox homeostasis can sense and transfer reducing equivalents to numerous target proteins, which is maintained by NAD(P) H-dependent thioredoxin and glutaredoxin systems and involved in various adverse environments (Meyer et al, 2012). In addition, several studies have revealed that glutathione (GSH) acts as an important protection system against metal stress in plants.…”
Section: Deps Between Pb1000-grown and Control Groupsmentioning
confidence: 99%